Nonlinear stress analysis of v-notched aluminum plates repaired with the wet patch technique - Saylik, Ahmet; Kaman, Mete Onur (Taylor & Francis Ltd, 2019)
In this study, V-notched aluminum plates were repaired using the wet patch technique. Two different repair operations, single-side and double-side composite patches, were applied to the notched plates. Four layers of woven carbon fiber textile and with the same reinforcement angle were used as a composite patch. Previously, the epoxy was saturated onto the prepared carbon fiber textiles and glued to the plates, and then those plates were placed in a vacuum medium. The repaired plates were experimentally tested under tension load. A nonlinear stress analysis was carried out using the finite element methodology in addition to the experimental results. As major foci of the study, the effects of repair type and notch size on failure behavior and plastic stress distribution were examined. As a result, it was found that the notch depth affects the repair performance far more than the notch width. Debonding failure load between the patch and the plate in plates repaired with a single-side patch was found to be two times higher than the yield load. For the double-side patch, the yield load was close to the debonding load and this repair method increases the debonding load more than a single-side patch.
Keywords: Aluminum and alloys; composites; finite element analysis; repair; stress analysis